HOW ONLINE LEARNING IS CHANGING TRADITIONAL CLASSROOMS - Saliyeva Ziroat Zokirovna; ErkinovaVisola (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
In recent years, online learning is becoming more common system of education due to its efficiency and useful sides. This transformation has not only enhanced accessibility and flexibility but has also redefined the roles of educators and students in the learning process. Traditional classrooms, long the cornerstone of educational systems, are now evolving to integrate digital technologies and online resources. However, traditional classrooms often provide opportunities for hands-on activities, such as experiments, physical education, or art projects, which are difficult to replicate in online settings. In this article, the differences, advantages and disadvantages of learning online and traditional system will be mentioned with possible examples.